The Impact of Information System Implementation in Enhancing the Effevtiveness and Efficiency of Travel management Business Process (A Study case in Total E & P Indonesia) - Arini, Cindy; Bangun, Yuni Ros (Journal of Business and Management, 2014)
Business Process Management (BPM) has long been used by organizations to improve their business process to be more effective and efficient in order to gain competitive advantage. Information Technology has been long acknowledged as one of the important role for BPM. One of the famous information technology implementation is Human Resource Information System (HRIS) that is used to support Human Resource business process especially in administration field. PT. Oil Diamond is one of the companies in Indonesia that implement HRIS to enhance their HR activity effectiveness and efficiency and currently adding new features called E-Travel Management. This research is conducted to analyze the impact of the implementation of E-Travel Management in enhancing the efficiency, how successful the new system produce output that met the user expectation with less cost and effort, and effectiveness, how successful the new system in solving the previous problem, of Travel Management business process in PT. Oil Diamond personnel administration services. Four independent variables was used in this research which are System Quality, Ease of Use, Information Quality and Usefulness and one dependent variables which is User Satisfaction. The result of the research shows E-Travel Management success in making the process of travel management more effective and efficient.Keywords: Business Process Management, HRIS, User Satisfaction, Information System Success